Park-people interface: a case study of Ayodhyapuri VDC, Chitwan, Nepal - Pant, Anita; Bhata, Shivraj (Scientific World, 2012)
The study in Ayodhyapuri Village Development Committee in Buffer Zone of Chitwan National Park revealed that the main source of energy is fuel wood, most of which is supplied from Buffer Zone Community Forestry (BZCF) and Chitwan National Park (37.93%) and partially from private land (2.15%). Agriculture was main source of livelihood among the villagers. Fuel wood consumption per household was found to be 3516.11 kg per year in the study area. Landless and low-income households were found using more fuel wood from BZCF and National Park. The root problems in the study area are the maximum extraction of fuel wood and fodder from the CF and National Park, and the crop depredation by wildlife. The depredation of the crop by wildlife is one of the major barriers influencing the conservation attitude of local people. The CF is rich in biodiversity as revealed by presence of 36 species of trees, 54 species of shrubs and 66 species of herbs. Shorea robusta is the most dominating species in both trees and shrub strata whereas Imperata cylindrica is the most frequent herbaceous species. Scientific World, Vol. 10, No. 10, July 2012 p47-53 DOI: http://dx.doi.org/10.3126/sw.v10i10.6862